Faktor-Faktor yang Mempengaruhi Kepuasan Pelanggan pada Hotel Tampiarto Kota Probolinggo - Novita Lidyana; Ika Wulandari (Fakultas Ekonomi dan Bisnis Islam, 2018)
Existence of existing tourism sector in Town probolinggo, encourage business actors to balance businessactivities by establishing hotels. Hotel Tampiarto is a hotel located in the center of Probolinggo City, at Jalan Suroyo No.15, Tisnonegaran, Kanigaran, Probolinggo City. This hotel has a very strategic place because it is located near the city of Probolinggo, Railway Station, KODIM 0820, Probolinggo Mayor's Office, and others. Because of its very strategic location, it gives advantages for Hotel Tampiarto to absorb many visitors. The services and facilities provided by Hotel Tampiarto Probolinggo can give a positive impression and negative impression for the visitors. The expected here is certainly a positive impression from visitors. To create a positive impression, of course Tampiarto Hotel has a strategy that is done to satisfy customers.